Functional Signalers of Changes in Visual Stimuli: Cortical Responses to Increments and Decrements in Motion Coherence. (25th September 2012) - Costagli, Mauro; Ueno, Kenichi; Sun, Pei; Gardner, Justin L.; Wan, Xiaohong; Ricciardi, Emiliano; Pietrini, Pietro; Tanaka, Keiji; Cheng, Kang
Abstract : How does our brain detect changes in a natural scene? While changes by increments of specific visual attributes, such as contrast or motion coherence, can be signaled by an increase in neuronal activity in early visual areas, like the primary visual cortex (V1) or the human middle temporal complex (hMT+), respectively, the mechanisms for signaling changes resulting from decrements in a stimulus attribute are largely unknown. We have discovered opposing patterns of cortical responses to changes in motion coherence: unlike areas hMT+, V3A and parieto-occipital complex (V6+) that respond to changes in the level of motion coherence monotonically, human areas V4 (hV4), V3B, and ventral occipital always respond positively to both transient increments and decrements. This pattern of responding always positively to stimulus changes can emerge in the presence of either coherence-selective neuron populations, or neurons that are not tuned to particular coherences but adapt to a particular coherence level in a stimulus-selective manner. Our findings provide evidence that these areas possess physiological properties suited for signaling increments and decrements in a stimulus and may form a part of cortical vigilance system for detecting salient changes in the environment.